Therapeutic effect of adalimumab in the treatment of intestinal Behçet's disease in children - Gao, Tianjiao; Ren, Xiaoxia; Han, Yanan; Wang, Fengfan; Liu, Bianhua; Fang, Ying (Frontiers in Pediatrics, 2025)
ObjectiveIntestinal Behçet's disease is a rare but severe manifestation of Behçet's disease, particularly in pediatric populations. Currently, there is no cure for intestinal Behçet's disease, and the goal of treatment is to control acute episodes and reduce inflammation. Adalimumab, a tumor necrosis factor-alpha (TNF-α) inhibitor, has shown promise in adult patients, but data on its efficacy and safety in children are limited. The aim of this study was to evaluate the efficacy and safety of adalimumab in the treatment of intestinal Behçet's disease in children.MethodsA retrospective analysis was conducted on 8 children with intestinal Behçet's disease treated with adalimumab at Xi'an Children's Hospital from January 2021 to December 2024. Clinical symptoms, endoscopic findings, and inflammatory markers were assessed before and after treatment. Efficacy was evaluated on the basis of symptom resolution, ulcer healing, and changes in inflammatory markers.ResultsThe cohort included 4 males and 4 females, with an average age of 11.9 ± 1.4 years and a disease course of 10.5 (6.75, 22.5) months. All patients presented with gastrointestinal symptoms, including abdominal pain (n = 7), vomiting (n = 1), and complications such as intestinal obstruction (n = 3) and perforation (n = 1). Colonoscopy revealed ileocecal ulcers in 7 patients and only terminal ileal ulcers in 1 patient. After treatment with adalimumab, complete resolution of clinical symptoms was observed in all patients. Gastrointestinal endoscopy revealed that 6 patients had completely healed ulcers, while the remaining 2 patients had ulcers that were reduced to 50% of their original size. The levels of inflammatory markers significantly decreased, with the erythrocyte sedimentation rate (ESR) decreasing from 44.63 ± 43.48 mm/h to 10.50 ± 7.65 mm/h (p = 0.046) and the high sensitivity C-reactive protein (hs-CRP) level decreasing from 43.87 ± 39.10 mg/L to 0.96 ± 0.67 mg/L (p = 0.017). On the basis of clinical symptoms and endoscopic findings, 6 patients (75%) achieved complete remission, and 2 patients (25%) showed improvement. Adalimumab was well tolerated, with only one case of mild eczema reported.ConclusionAdalimumab is safe and effective in the treatment of intestinal Behçet's disease in children.